A new species of Mud Snake (Serpentes, Homalopsidae, Gyiophis Murphy & Voris, 2014) from Myanmar with a first molecular phylogenetic assessment of the genus - Quah, Evan S.h.; Grismer, L. Lee; Wood, Perry L., Jr.; Thura, Myint Kyaw; Zin, Thaw; Kyaw, Htet; Lwin, Ngwe; Grismer, Marta S.; Murdoch, Matthew L. (Zootaxa, 2017)
A newly discovered species of homalopsid snake from the genus Gyiophis Murphy & Voris is described from the lowlands of Mawlamyine District in Mon state, southeastern Myanmar. Gyiophis salweenensis sp. nov. is presumed to be closely related to G. maculosa Blanford and G. vorisi Murphy based on the similarities in pholidosis and patterning but can be separated from G. maculosa by the shape of its first three dorsal scale rows that are square, ventral scale pattern that lacks a central spot, and a faint stripe on dorsal scale rows 1–4. It can be further distinguished from G. vorisi by its lower number of ventral scales (129 vs. 142–152), lower number of subcaudals (30/29 vs. 41–58), narrow rostral scale, and having more rows of spots on the dorsum (four vs. three). A preliminary molecular analysis using 1050 base pairs of cytochrome b (cytb) recovered G. salweenensis sp. nov. as the sister species to the Chinese Mud Snake (Myrrophis chinensis). G. maculosa and G. vorisi were unavailable for the analysis. The discovery of G. salweenensis sp. nov. highlights the need for more surveys into the herpetological diversity of eastern Myanmar which remains very much underestimated.